THE ROLE OF ENDOCRINE DISRUPTORS IN EARLY PUBERTY AND HORMONAL IMBALANCES IN WOMEN - Weronika Skoczek, (International Journal of Innovative Technologies in Social Science, 2025)
In recent decades, puberty has been occurring at younger ages, particularly among girls. While genetics and nutrition are well-known influences, increasing evidence suggests that endocrine-disrupting chemicals (EDCs) also play a role. EDCs are compounds that interfere with hormones by mimicking, blocking, or altering their activity. Found in plastics, cosmetics, pesticides, and processed foods, they represent widespread, unavoidable exposures in modern life.Early puberty carries significant health risks beyond physical changes. Girls who mature earlier are more likely to develop hormonal imbalances, menstrual irregularities, metabolic disorders, and reproductive conditions such as polycystic ovary syndrome, endometriosis, and infertility. Prolonged estrogen exposure is also linked to hormone-sensitive cancers. Metabolic disruptions may further increase risks of obesity, insulin resistance, and cardiovascular disease.Evidence on EDCs remains mixed: some studies associate higher levels of bisphenol A, phthalates, and parabens with early puberty, while others report inconsistent effects. Variability may stem from genetic susceptibility, metabolism, or cumulative exposure to environmental factors.This review explores how EDCs may influence pubertal timing and long-term hormonal health, emphasizing the need to recognize environmental contributors to female reproductive development and to strengthen the regulation of endocrine-disrupting chemicals.